Lesion extent negatively impacts intellectual skills in pediatric focal epilepsy - Stefanos-Yakoub, Ilona; Wingeier, Kevin; Cserpan, Dorottya; Gennari, Antonio Giulio; Latal, Beatrice; Reuner, Gitta; Ramantani, Georgia (Pediatric neurology, 2023)
Background - Cognitive development in children and adolescents with focal lesional epilepsy is determined by the underlying epileptogenic lesion, in addition to epilepsy itself. However, the impact of lesion-related variables on intelligence quotient (IQ) and developmental quotient (DQ) remains largely unexplored. Here, we aimed to determine the effect of lesion-related predictors and their relation with epilepsy-related predictors of intellectual functioning. - Methods - We retrospectively analyzed data from children with focal lesional epilepsy who underwent standardized cognitive evaluation yielding IQ/DQ in our institution. - Results - We included 50 consecutive patients aged 0.5 to 17.5 years (mean, 9.3; S.D., 4.9) at cognitive assessment. Epilepsy duration was 0 to 15.5 years (mean, 3.8; S.D., 4.1). Of the total cohort, 30 (60%) patients had unilobar lesions, seven (14%) multilobar, 10 (20%) hemispheric, and three (6%) bilateral. Etiology was congenital in 32 (64%) cases, acquired in 14 (28%), and progressive in four (8%). For patients with unilobar lesions, the mean IQ/DQ was 97.1 ± 15.7, for multilobar 98.9 ± 20.2, for hemispheric 76.1 ± 20.5, and for bilateral 76.3 ± 4.5. Larger lesion extent, earlier epilepsy onset, and longer epilepsy duration correlated with lower IQ/DQ in the univariate analysis, whereas only lesion extent and epilepsy duration contributed significantly to the explanatory model in the multivariable analysis. - Conclusions - The present study demonstrates that lesion extent and epilepsy duration are important risk factors for intellectual impairment in pediatric patients with focal lesional epilepsy. These findings are useful for family counseling and the early consideration of interventions that may limit the duration of epilepsy.